Graphene-based nanomaterials for drug and/or gene delivery, bioimaging, and tissue engineering. Issue 9 (September 2017) - Zhao, Hong; Ding, Ruihua; Zhao, Xin; Li, Yiwei; Qu, Liangliang; Pei, Hao; Yildirimer, Lara; Wu, Zhengwei; Zhang, Weixia
Highlights: Graphene-based nanomaterials are emerging as the next generation's candidates for biotechnological advancements. Graphene and its various derivatives have been covered. The properties of graphene-based materials related to biomedical applications have been discussed. The review emphasizes the up-to-date biomedical applications of graphene-based materials. It also covers the rising concern about the toxicity of graphene-based materials. Abstract : Here, we discuss the biomedical applications of graphene-based nanomaterials (GBNs). We examine graphene and its various derivatives, including graphene, graphene oxides (GOs), reduced graphene oxides (rGOs), graphene quantum dots (GQDs), and graphene composites, and discuss their unique properties related to their biomedical applications. We also summarize the detailed biomedical applications of GBNs, including drug and/or gene delivery, bioimaging, and tissue engineering. We also highlight the toxicity of these nanomaterials.